2019
DOI: 10.1128/mcb.00138-19
|View full text |Cite
|
Sign up to set email alerts
|

EWSR1-FLI1 Activation of the Cancer/Testis Antigen FATE1 Promotes Ewing Sarcoma Survival

Abstract: Ewing sarcoma is characterized by a pathognomonic chromosomal translocation that generates the EWSR1-FLI1 chimeric transcription factor. The transcriptional targets of EWSR1-FLI1 that are essential for tumorigenicity are incompletely defined. Here, we found that EWSR1-FLI1 modulates the expression of cancer/testis (CT) antigen genes, whose expression is biased to the testes but is also activated in cancer. Among these CT antigens, fetal and adult testis expressed 1 (FATE1) is most robustly induced. EWSR1-FLI1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 55 publications
(58 reference statements)
0
18
0
Order By: Relevance
“…Cells were seeded at a density of 50,000 cells (HCC515) or 5000 cells (H2122) per 12-well plate and treated as previously described ( Gallegos et al, 2019 ). After 3 weeks, colonies were stained overnight with 0.01% crystal violet.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were seeded at a density of 50,000 cells (HCC515) or 5000 cells (H2122) per 12-well plate and treated as previously described ( Gallegos et al, 2019 ). After 3 weeks, colonies were stained overnight with 0.01% crystal violet.…”
Section: Methodsmentioning
confidence: 99%
“…These data indicated that EWS-FLI1 directly activates the expression of the CT antigen FATE1 as a means of supporting ES sarcoma tumor cell survival. 93 Performing a database homology search CT antigen XAGE-1 was found to be expressed in ES. 94 Later, Liu et al found XAGE-1 to be expressed in 7/8 ES cell lines and in 4/9 ES patient samples.…”
Section: The Search For Tumor Targets: Intracellular Antigensmentioning
confidence: 99%
“…As explained previously, ES is characterized by a pathognomonic chromosomal translocation that generates the EWS–FLI1 chimeric transcription factor; however, the transcriptional targets of EWS–FLI1 that are essential for tumorigenicity are incompletely defined. In a very recent study, Gallegos et al 93 found that EWS–FLI1 modulates the expression of a certain class of immunogenic tumor-associated genes, so-called cancer-testis (CT) antigens. Among CT antigens, the expression of which is typically restricted to germ cells and cancer cells, fetal and adult testis expressed 1 (FATE1) was found to be the most robustly induced in ES.…”
Section: The Search For Tumor Targets: Intracellular Antigensmentioning
confidence: 99%
See 1 more Smart Citation
“…FATE1 is expressed at high levels in about 40% of adult ACC and its expression is significantly and inversely correlated with patients' overall survival (OS) [5]. Additionally, FATE1 silencing increased sensitivity of the NCI-H1155 non-small lung cancer cell line to paclitaxel [6] and reduced viability of a variety of other cancer cell lines [7,8].…”
Section: Introductionmentioning
confidence: 99%